Electron microscopic observation of photoreceptor cells in directly inserted anesthetized Drosophila into a high‐pressure freezing unit. Issue 3 (23rd December 2018) - Terada, Hitomi; Saitoh, Yurika; Kametani, Kiyokazu; Sakaguchi, Masahiko; Sakamoto, Takeharu; Kamijo, Akio; Terada, Nobuo
Abstract: The high‐pressure freezing (HPF) technique is known to cryofix water‐containing materials with little ice‐crystal formation in deep depths compared with other freezing techniques. In this study, HPF for anesthetized living Drosophila was performed by placing them directly on the carrier of the HPF unit and exposing them to light. Frozen Drosophila were freeze substituted, and their compound eyes were examined by transmission electron microscopy. The ultrastructures of ommatidia composed of photoreceptor cells were well preserved. The location of the cytoplasmic organelles inside the photoreceptor cells was observed. In some photoreceptor cells in ommatidia of the light‐exposed Drosphila, the cytoplasmic small granules were localized nearer the base of rhabdomeres, compared with those of the nonlight‐exposed Drosophila . Thus, HPF with the direct insertion of living Drosophila under light exposure into the HPF machine enabled us to examine changes to functional structures of photoreceptor cells that occur within seconds. Abstract : Living Drosophila were directly inserted into the high‐pressure freezing machine. Wide areas of compound eyes were observed without obvious ice‐crystal formation. Organelle localization in photoreceptor cells under light stimulation was detected.